Analisis Strategi Segmenting, Targeting dan Positioning Pengaruhnya terhadap Keputusan Konsumen Menggunakan Produk Hijab Merek Azara - Deni Irfa Yanti; Ety Saraswati (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2020)
The purpose of this study is to determine empirical evidence about the effect of strategy Segmentation, Targeting, and Positioning of Product Brand Purchasing Decisions azara brand hijab at a lecturer at the University of Islam Malang. The research method in this research is to use the linear regression method with the processed data are Segmenting (X1), Targeting (X2), Positioning (X3) and Decision Purchase (Y). This type of research is explanatory associative with quantitative approach. In this study, the population is a lecturer at the University of Islam Malang the number of samples used by 100 respondents. The analytical method used in this study is multiple regression. Data analysis technique used multiple regression analysis technique using SPSS version 24.00. Research result shows that the coefficient of determination (R2) that of all the independent variables Segmenting (X1) Targeting (X2) and Positioining (X3) have the ability to explain variations of the decision dependent variable Purchase (Y) of 0.145 or 14.5% while the remaining 0.855 or 85.5% is explained by variables other. There is a significant effect of the Segmenting (X1) Targeting (X2) and Positioning (X3) variables simultaneously affect the dependent variable, namely the Purchase Decision (Y).